1995
DOI: 10.1161/01.cir.91.10.2596
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Varying Intensities and Formats of Physical Activity on Participation Rates, Fitness, and Lipoproteins in Men and Women Aged 50 to 65 Years

Abstract: While older adults can benefit from initiating a regular regimen of moderate-intensity exercise in terms of improved fitness levels and small improvements in HDL cholesterol levels, the time frame needed to achieve HDL cholesterol change (2 years) may be longer than that reported previously for younger populations. Frequency of participation may be particularly important for achieving such changes. Supervised home-based exercise regimens represent a safe, attractive alternative for achieving sustained particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
243
5
14

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 462 publications
(293 citation statements)
references
References 27 publications
31
243
5
14
Order By: Relevance
“…In prior studies it has been demonstrated that printbased materials that are individualized, motivationally tailored, and emphasize key social cognitive concepts such as self-efficacy and outcome expectations are effective tools for enhancing physical activity adoption [10,14]. Prior studies have also shown that telephonebased interventions emphasizing social cognitive concepts have demonstrated short-and longer-term efficacy [9,16,57,58]. Thus, the purpose of this study is to examine the relative efficacy of two different channels for delivering a computerized expert-system guided intervention (i.e., print vs. telephone) for physical activity as well as the relative cost of each intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In prior studies it has been demonstrated that printbased materials that are individualized, motivationally tailored, and emphasize key social cognitive concepts such as self-efficacy and outcome expectations are effective tools for enhancing physical activity adoption [10,14]. Prior studies have also shown that telephonebased interventions emphasizing social cognitive concepts have demonstrated short-and longer-term efficacy [9,16,57,58]. Thus, the purpose of this study is to examine the relative efficacy of two different channels for delivering a computerized expert-system guided intervention (i.e., print vs. telephone) for physical activity as well as the relative cost of each intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The use of such an expert system to guide program content is unique in the telephone delivery arena, and, if found to be effective, might expand such counseling to health interveners with less specific or formal training or education in the telephone counseling arena (given that the content for each call was structured using the compiled expert system information). Research indicates that both print and telephone-based physical activity interventions are efficacious (e.g., [9,60]); however, no study to our knowledge has examined both interventions within the same clinical trial. The telephone and print interventions included the same content but differed on a few factors related to the delivery channel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are equivocal data regarding the influence of exercise intensity on adherence/compliance [36], it should be noted that the overwhelming barrier to regular exercise participation is lack of time [37]. This finding is ubiquitous; regardless of age, ethnicity, sex or health status, individuals report that a lack of time is the primary reason for their failure to exercise on a regular basis [38,39].…”
Section: The Study's Findingsmentioning
confidence: 99%